Fueling Gender Stereotypes: A Content Analysis of Automobile Advertisements. Issue 2 (July 2019) - Sandhu, Namrata
Abstract: Cultivation analysis is an established methodology to comprehend the impact of gender stereotypy in television commercials on the viewers and society. Taking India as a case in point, the current study utilizes this framework to examine the use of gender in television commercials for automobiles ( n = 84). Taped television commercials were examined across four content analytic measures: (a) ad orientation, (b) gender of voice-over, (c) gender of a dominant product user, and (d) gender of the main character. The procedures for coding and assessment of the reliability of coding were modeled on existing methodologies. The proportionality criterion was used to analyze the data. Results indicate a strong gender preference for the male gender in television commercials for automobiles. A comparison between the automobile and non-automobile advertisements establishes a significantly higher gender preference in automobile advertisements than non-automobile advertisements. The study demonstrates the complementarity between a primary data-based analysis and existing literature on the subject. Implications are discussed.